2014
DOI: 10.1158/1535-7163.mct-13-0962
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Integrin α6 Stimulates Curative-Type Bone Metastasis Lesions in a Xenograft Model

Abstract: Laminin binding integrin receptors are key mediators of epithelial cell migration and tumor metastasis. Recent studies have demonstrated a role for the alpha 6 integrin (ITGA6/CD49f) in maintaining stem cell compartments within normal bone marrow and in residency of tumors metastatic to bone. In this study, we tested a function-blocking antibody specific for ITGA6, called J8H, to determine if pre-existing cancer lesions in bone could be slowed and/or animal survival improved. Human prostate tumors were establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Recent work shows the functional role of one LBI (α6β4) as a mediator of endothelial cell protection in the setting of excessive mechanical stretch relative to lung injury [63]. LBI expression patterns have clinical significance for several epithelial-derived malignancies, for example the α6β1 integrin receptor is conserved in prostate cancer [39], is expressed on prostate tumor cells undergoing PNI [13], and acts as a marker in the aggressive phenotype of tumor cells during cancer progression [14,32,60,64]. The LBIs are especially associated with the invasion and metastasis of human prostate cancer, traversing through muscle [39,6569].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work shows the functional role of one LBI (α6β4) as a mediator of endothelial cell protection in the setting of excessive mechanical stretch relative to lung injury [63]. LBI expression patterns have clinical significance for several epithelial-derived malignancies, for example the α6β1 integrin receptor is conserved in prostate cancer [39], is expressed on prostate tumor cells undergoing PNI [13], and acts as a marker in the aggressive phenotype of tumor cells during cancer progression [14,32,60,64]. The LBIs are especially associated with the invasion and metastasis of human prostate cancer, traversing through muscle [39,6569].…”
Section: Resultsmentioning
confidence: 99%
“…It is currently unknown how the variant participates in cohesive tumor clusters and whether the co-localization of uPAR and α6 integrin in prostate cancer tissue would reveal aggressive subclasses of Gleason grade 6 (3+3) tumors. We have shown that preventing α6p production in prostate tumor clusters within the bone arrests bone lesion progression, resulting in curative-type lesions [64]. Considering that approximately 85% of patients with advanced disease develop bone metastases, preventing α6p production may represent a novel, non-cytotoxic treatment for prostate cancer patients with advanced disease and extensive skeletal involvement; alternatively, blocking the function of the laminin-adhesion receptors can stimulate curative-type bone metastasis lesions [64].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies by our group have identified a cleaved form of ITGA6, called ITGA6p, which has been shown to contribute to cell invasion and migration [13]. Inhibition of ITGA6 cleavage substantially delayed the onset of bone metastasis and promoted curative-type bone metastasis lesions in xenograft mouse models [14,15]. Due to the high prevalence and pro-metastatic phenotype of ITGA6p, we further investigated selected molecular candidates as modifiers of ITGA6p production.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that tumor activated macrophages promote prometastatic integrin-dependent pericellular proteolysis and the metastatic phenotype [12]. Furthermore, ITGA6 cleavage has been shown to contribute to cell invasion and migration on laminin, and inhibition of ITGA6 cleavage was shown to substantially delay the onset of bone metastasis and promote curative-type bone metastasis lesions in xenograft mouse models [1315]. In addition to the role of extracellular regulators in ITGA6p production, our group has shown that cleavage of ITGA6 was dependent on actin [16].…”
Section: Introductionmentioning
confidence: 99%